Optimization method of boosted frequency starting asynchronous gyroscope engine with fixed restriction and minimum current - Повстень, В. А.; Аузеллаг, Д. (Proceedings of National Aviation University (archive), 2000)
Designed is a method of determining optimal regularities of frequency and voltage regulation in frequence boosted starting of asynchronous gyroscope engine under fixed power restrictions minimum current and also under some other restrictions